2015
DOI: 10.1242/jeb.125443
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition and expression of memories of distance and direction in navigating wood ants

Abstract: Wood ants, like other central place foragers, rely on route memories to guide them to and from a reliable food source. They use visual memories of the surrounding scene and probably compass information to control their direction. Do they also remember the length of their route and do they link memories of direction and distance? To answer these questions, we trained wood ant (Formica rufa) foragers in a channel to perform either a single short foraging route or two foraging routes in opposite directions. By sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Our proposed encoding of GVs is validated by recent findings from a behavioral study on wood ants (Fernandes et al, 2015). The authors carried out a series of novel experimental paradigms involving training and testing channels.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our proposed encoding of GVs is validated by recent findings from a behavioral study on wood ants (Fernandes et al, 2015). The authors carried out a series of novel experimental paradigms involving training and testing channels.…”
Section: Discussionsupporting
confidence: 73%
“…For GVs, the context is determined by the foraging state, which we model as a binary unit. Indeed, behavioral studies on desert (Wehner et al, 2006) and wood ants (Fernandes et al, 2015) have shown that expression of spatial memories is controlled by an internal state in a binary fashion. The association of the context with a reward signal, received at the feeder, drives synaptic weight changes corresponding to the difference between the current PI state and the respective weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposed encoding of GVs is validated by recent findings from a behavioral study on wood ants [76]. The authors carried out a series of novel experimental paradigms involving training and testing channels.…”
Section: Reward-modulated Vector Acquisition and The Role Of Motivatimentioning
confidence: 65%
“…For GVs, the context is determined by the foraging state, which we model as a binary unit. Indeed, behavioral studies on desert [75] and wood ants [76] have shown that expression of spatial memories is controlled by an internal state in a binary fashion. The association of the context with a reward signal, received at the feeder, drives synaptic weight changes corresponding to the difference between the current PI state and the respective weight.…”
Section: Reward-modulated Vector Acquisition and The Role Of Motivatimentioning
confidence: 99%